Extra sound attenuation via shunted piezoelectric resonators in a duct. (1st July 2022) - Liu, Xiang; Wang, Chunqi; Zhang, Yumin; Wu, Keming; Dong, Bin; Huang, Lixi
Highlights: A smart side-branch silencer is investigated based on piezoelectric (PZT) resonators The coupling and PZT arrays optimization are studied by a Finite Element Model The electrical peaks by PZTs work at low frequencies without more volume requirement The extra attenuation peaks by light PZTs are net gain based on plate silencer Abstract: A smart side-branch silencer controlled by shunted piezoelectric (PZT) resonators is investigated. Several PZT resonators are mounted behind a thin plate constituting a part of the wall of a flow duct and being backed by a cavity, and they interact with the sound waves in the duct to optimise the vibroacoustic interaction and improve the effect of sound attenuation at low frequencies. This smart silencer can filter out the selected incident waves without flow blockage, and the filtering characteristic can be controlled electrically via the piezoelectric patch arrays shunted with semi-passive circuits. A three-dimensional (3D) finite element model is constructed to study the effects of damping and electromechanical coupling on the proposed smart silencer, and experiments are conducted to test the performance of this silencer. Both simulated and measured results demonstrate that extra resonant peaks can be added from the electrical resonances without significant negative impacts on the sound attenuation associated with the plate resonances. As shunt circuits do not occupy much physical space, such additional peaks represent a net gain based on the performance of the plate silencer. Graphical abstract: Image, graphical abstract